Da un ponte all'altro - Baldassini, Niccolo (L'Arca, 1998)
Cuatro puentes peatonales por: - Embankment Renaissance Footbridge, Bedford. - Tyne Millennium Bridge, Gateshead. - South Dock Footbridge, London y - Hammarby Canal Bridge, Stockholm.